2019
DOI: 10.3390/genes10100766
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Bioinformatics Resources Reveals the Therapeutic Benefits of Gemcitabine and Cell Cycle Intervention in SMAD4-Deleted Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the most common and aggressive type of pancreatic cancer. The five-year survival rate of PDAC is very low (less than 8%), which is associated with the late diagnosis, high metastatic potential, and resistance to therapeutic agents. The identification of better prognostic or therapeutic biomarker may have clinical benefits for PDAC treatment. SMAD4, a central mediator of transforming growth factor beta (TGFβ) signaling pathway, is considered a tumor suppressor gene. SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…In advanced pancreatic cancers treated by gemcitabine, SMAD4 loss had no impact on OS (HR 1.008; p = 0.656) but was associated with a prolonged PFS (HR 1.565, p = 0.038) [70]. Recently, an analysis of publicly available datasets from The Cancer Genome Atlas (TGCA) indicated that PDAC patients with a deleted SMAD4 gene had poorer DFS; however, SMAD4 alterations did not predict the OS [71]. In another study, SMAD4 expression status was neither associated with early death (OR 0.5; p = 0.15) nor associated with recurrence pattern (OR 0.9; p = 0.9) in patients with resected PDAC [72].…”
Section: Effect Of Smad4 Expression In Patients With Pdacmentioning
confidence: 99%
See 1 more Smart Citation
“…In advanced pancreatic cancers treated by gemcitabine, SMAD4 loss had no impact on OS (HR 1.008; p = 0.656) but was associated with a prolonged PFS (HR 1.565, p = 0.038) [70]. Recently, an analysis of publicly available datasets from The Cancer Genome Atlas (TGCA) indicated that PDAC patients with a deleted SMAD4 gene had poorer DFS; however, SMAD4 alterations did not predict the OS [71]. In another study, SMAD4 expression status was neither associated with early death (OR 0.5; p = 0.15) nor associated with recurrence pattern (OR 0.9; p = 0.9) in patients with resected PDAC [72].…”
Section: Effect Of Smad4 Expression In Patients With Pdacmentioning
confidence: 99%
“…A study showed that SMAD4-deficient cell lines are modestly less sensitive to gemcitabine and 2.0-fold and 4.5-fold more sensitive to cisplatin and irinotecan, respectively [73]. Controversially, a recent study found that SMAD4-deleted PDAC cells are more sensitive to gemcitabine, while SMAD4 mutated cells had similar sensitivity to gemcitabine as SMAD4 wild-type cells, suggesting that the SMAD4 copy number could be used as a therapeutic biomarker for PDAC treatment with gemcitabine [71]. This study also found that SMAD4-deleted PDAC cells are sensitive to other agents modulating the cell cycle including cytarabine, clofarabine, darinaparsin, and olaparib, due to the upregulation of cell cycle-related genes such as CDK1 [71].…”
Section: Smad4 As a Potential Target In Patients With Pdac And Impact On Othermentioning
confidence: 99%
“…The expression of the SMAD4 protein has been positively associated with an increased survival and negatively associated with the grade of intraepithelial lesions [ 87 , 93 ]. Interestingly, SMAD4 deletion has been associated with a shorter disease-free survival without affecting the overall survival [ 94 ]. A meta-analysis by Shugang and colleagues revealed an increased risk of death in PDAC patients with SMAD4 deletion, in both univariate (hazard ratio: 1.20; 95% CI: 1.03–1.40) and multivariate analysis (hazard ratio: 1.88; 95% CI: 1.31–2.70) data pooling [ 95 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated a role of SMAD deletion in the promotion of radioresistance in PDAC cells through the activation of autophagy and the clearance of radiation-induced cytotoxic oxidative products [ 96 ]. Notably, decreased SMAD expression results in an increased sensitivity of PDAC to drugs that target the cell cycle, including gemcitabine and cytarabine [ 94 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…To date, however, early-phase clinical trials evaluating TGF-β inhibitors (e.g., galunisertib) have shown only modest efficacy in PDAC [ 62 ]. In this Special Issue, Hsieh et al leveraged publicly available datasets to show that SMAD4 deletion is associated with shorter disease-free survival in PDAC [ 63 ]. They also showed that SMAD4 -deleted PDAC cells have increased sensitivity to cell cycle-targeting drugs due to upregulation of cell cycle-related genes.…”
Section: Somatic Alterations In Pdac: Drugging “Undruggable” Drivementioning
confidence: 99%